2022
DOI: 10.1007/s10668-022-02700-0
|View full text |Cite
|
Sign up to set email alerts
|

The analytic hierarchy process as an innovative way to enable stakeholder engagement for sustainability reporting in the food industry

Abstract: The sustainable transition, which requires a combination of natural and human resources to foster the development and protection of ecosystems, is a challenge of civil society. New approaches may be proposed to support enterprises in identifying the appropriate strategic criteria for their sustainability initiatives, which are eventually documented in corporate sustainability reports. The present paper focuses on the food industry, particularly with regard to pasta production.The analytic hierarchy process met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Specifically, the results showed that the sustainability course was essential for changing students’ sustainability attitudes and behaviours. The findings support the model of a sustainable community based on stakeholder engagement, which can fundamentally change even industrial systems 44 . However, sustainable communities require support from HEIs 26 , which in turn need to connect to the outside world 52 and embrace change, on the basis of dynamic competencies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Specifically, the results showed that the sustainability course was essential for changing students’ sustainability attitudes and behaviours. The findings support the model of a sustainable community based on stakeholder engagement, which can fundamentally change even industrial systems 44 . However, sustainable communities require support from HEIs 26 , which in turn need to connect to the outside world 52 and embrace change, on the basis of dynamic competencies.…”
Section: Discussionsupporting
confidence: 74%
“…See questions 10–16 in supplementary A ppendix A). The decision to include these items was based on previous research showing associations between: (i) playing sports and volunteering and greater sustainable behaviour 42 , 43 , and (ii) engagement with nature and improved stakeholder engagement 44 ; as well as the use of recycling, using sustainable products and taking public transportation as proxies of pro-environmental attitudes 45 . An index was created to average student scores on these six items and assess any correlation with character aspects (i.e., altruism).…”
Section: Resultsmentioning
confidence: 99%
“…This method is also used to evaluate the blockchain in terms of risk [51]. In addition, MCDA is supported by the Analytic Hierarchy Process (AHP) when it is necessary to provide quantitative assessments based on expert background to select the most relevant criteria [52].…”
Section: The Context Of Analysismentioning
confidence: 99%
“…A criterion is selected if it appears in at least half of the works analyzed (three out of five). In a context where the number of criteria is at most 10, a classical AHP is used; however, if more criteria are identified, the local-global priority method of AHP should be used [52].…”
Section: Identification Of Critical Criteriamentioning
confidence: 99%
“…There are advanced models and technology as an innovative way to enable stakeholder engagement for sustainability reporting in the food industry (D'Adamo, 2022). Nature‐based solutions (NbS), along with innovative ideas and technologies, are urgent requirements of agricultural practices to foster development and avoid the destruction of the natural environment (D'Adamo, 2022). There is a need for non‐destructive assessment and monitoring of the field soil condition and crop conditions, which could be monitored using geospatial technology, about precision agriculture to achieve food security.…”
Section: Food Security Problem and Solutionmentioning
confidence: 99%